Deciphering Consumer Behavior in Online Retail with Data Driven Analytical Exploration - Muhammad Zulkifl Hasan; Muhammad Zunnurain Hussain; Hafiz Muhammad Ishtiaq; Hooria Umar; Talha Asif; Abubaker Siddique; Jibran Ali, (Dialogue Social Science Review (DSSR), 2025)
Online retailers should study customer behavior to strengthen their digital presence and sales techniques. This research uses data to analyze online purchase customer behavior dynamics. This study uses sophisticated analytics to find patterns and trends in a huge dataset from several e-commerce platforms that affect consumer interactions and purchase choices. The research analyzes customer behavior (both browsing and purchasing), how digital marketing methods affect buying decisions, and how social media affects consumer behavior. Demographic differences, such as gender, age, and geography, also affect online customers, according to the study. The research uses machine learning algorithms to anticipate customer preferences and behavior. This provides vital data for internet companies to customize their products to customers' tastes. The study also examines online buyers' mental states. These criteria include reviews and ratings, internet shopping ease, and trust. Further, the research examines the possibilities and constraints of new technologies like augmented reality and AI-driven tailored suggestions. It also discusses how these technologies may revolutionize online shopping. Overall, e-commerce enterprises, marketers, and politicians may profit from this research on online purchasing consumer behavior dynamics. These findings underpin customer-focused online buying tactics. Understanding the multifaceted nature of digital clients' behavior may help companies adjust to the digital marketplace's ever-changing expectations.